1997
DOI: 10.1046/j.1365-2257.1997.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Haematological reference ranges for schoolchildren

Abstract: There are few reports of reference ranges for haematological values in school age children and most studies extend over a small age range or have excluded a considerable proportion of the study population in an effort to omit those with haemoglobinopathies or anaemia. Blood samples from 2135 children aged 4-19 years, from randomly selected schools, were analysed by automated counter. Reference ranges for red cell, white cell and platelet indices are provided from the results. Median haemoglobin and red blood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

25
79
4
14

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(122 citation statements)
references
References 0 publications
25
79
4
14
Order By: Relevance
“…Similar to other studies, we found that platelet count decreased with age during childhood (24 ) and that adult women had slightly higher counts than men, but levels tended to decrease with age in both sexes (2,25 ). Thrombopoietin, a hormone that regulates production of platelets, has been found to peak shortly after birth and gradually decline to adult concentrations (26 ), which could explain the higher platelet counts observed in early childhood.…”
Section: Discussionsupporting
confidence: 76%
“…Similar to other studies, we found that platelet count decreased with age during childhood (24 ) and that adult women had slightly higher counts than men, but levels tended to decrease with age in both sexes (2,25 ). Thrombopoietin, a hormone that regulates production of platelets, has been found to peak shortly after birth and gradually decline to adult concentrations (26 ), which could explain the higher platelet counts observed in early childhood.…”
Section: Discussionsupporting
confidence: 76%
“…5,12,19,24,26 Environmental factors and altitude also influence the value of hematological parameters. 10 Saudi Arabia forms the largest part of the Arabian Peninsula and occupies over 2.2 million square kilometers. 33 It is probably among the driest countries in the world, with long, hot and almost totally dry summers, and a short very cool winter season during which rain occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies during the last three to four decades conducted in different populations have worked out normal reference ranges for hematological parameters in adults and children, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and have reported significant differences in different ethnic groups. 3,5,12,14,18,24,26 In African-American, African and Afro-Caribbean children, the levels of these parameters are generally lower than in Caucasians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, appropriate diagnosis and treatment can reduce the infant and children morbidity and mortality rates [10]. In several studies significant differences in hematology reference range have been found in children at various ages and adolescents in different populations, seasons, racial ethnic groups, and gender subgroups [11,12].…”
Section: Discussionmentioning
confidence: 99%